Pengaruh Protégé Career Optimism, Mentoring Relationship, Self-Efficacy, Dan Emotional Intelligence Terhadap Oganizational Commitment Pada Karyawan Minimarket di Jakarta Selatan - Kurniawan, Aziza Idris; Kanissa, Rininta Andriani; Emilisa, Netania; Putri, Gede Mahira (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the influence of Protégé Career Optimism, Mentoring Relationship, Self-Efficacy, and Emotional Intelligence on Organizational Commitment. The research was conducted using a quantitative approach and survey method by taking samples from employees at several Minimarkets in Jalan South Jakarta. Data were analyzed using multiple regression analysis techniques. Collected a sampel of 229. The results showed that Protégé Career Optimism, Mentoring Relationship, significantly influenced Organizational Commitment. However, Self-Efficacy, and Emotional Intelligence do not significantly affect Organizational Commitment. These findings suggest that employees who have high levels of Protégé Career Optimism, strong Mentoring Relationship, high Self-Efficacy, and good Emotional Intelligence tend to have a higher commitment to the organization where they work. This research provides practical implications for companies in increasing employee commitment. Company management can pay attention to the factors that influence employee commitment. By improving these factors, companies can increase employee commitment and reduce turnover rates. This research also makes a theoretical contribution to the literature on organizations, as it reveals the importance of psychological factors in shaping employee commitment.